Copper-clad plate for printed circuit board and preparation method of copper-clad plate

By combining phenolic epoxy resin with end vinyl polyphenylene ether and silicone modification on the surface of the silica, bifunctional silicon dioxide is prepared as a crosslinking agent to form a new resin with a crosslinked mesh structure through the epoxy resin, the problem of insufficient dielectric performance of copper clad plate in high-frequency environments is solved, and higher heat resistance and mechanical properties are achieved.

CN119730009AActive Publication Date: 2025-03-28SHENZHEN LINGHANGDA ELECTRONICS CO LTD

Patent Information

Application Number
CN202510220486.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The existing copper clad plate has large dielectric constant and dielectric loss in high-frequency environments, and lacks heat and humidity resistance, which affects its application performance.

Method used

A phenolic epoxy resin is combined with end vinyl polyphenylene ether, and silicone modification is performed on the surface of the silica to prepare bifunctional silicon dioxide as a crosslinking agent to form a new resin with a cross-linked network structure throughout the epoxy resin.

Benefits of technology

It significantly reduces the dielectric constant and dielectric loss of the copper clad plate, improves its heat resistance and mechanical properties, and enhances the bonding strength between the glass fiber cloth and the resin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The invention discloses a copper-clad plate for a printed circuit board and a preparation method of the copper-clad plate, and relates to the technical field of printed circuit board materials. The invention discloses a preparation method of a copper-clad plate for a printed circuit board, which comprises the following steps of: soaking a reinforcing material in a glue solution, and drying to obtain a prepreg; carrying out hot-pressing treatment on the prepreg and copper foil to obtain a copper-clad plate; the glue solution comprises the following raw materials in parts by weight: 15-20 parts of vinyl-terminated polyphenyl ether, 20-25 parts of epoxy resin, 20-25 parts of difunctional silicon dioxide, 15-25 parts of an organic solvent, 0.3-0.6 part of a curing agent and 0.05-0.1 part of a curing accelerator; the difunctional silicon dioxide cross-linked polyphenyl ether and epoxy resin prepared by the preparation method disclosed by the invention are used as a resin material of a glue solution, and have the characteristics of good heat resistance and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of printed circuit board materials, and in particular to a copper clad plate for a printed circuit board and a preparation method thereof. Background Art

[0002] Copper-clad laminate is a composite material made of electronic-grade glass fiber cloth or other reinforcing materials and resin, and coated with copper foil on one or both sides, and made by hot pressing. It is referred to as copper-clad laminate. After subsequent selective cutting, etching, drilling and metallization processes, the copper-clad laminate can be made into printed circuit boards that meet different requirements. The copper-clad laminate has three main functions for printed circuit boards: signal transmission, insulation and support. Therefore, the quality of the copper-clad laminate directly affects the performance, quality, processability in manufacturing and durability of the printed circuit board. Its performance depends to a large extent on the dielectric constant and dielectric loss value of the substrate. This is because the transmission speed of the signal in the printed circuit board is and power loss Closely related to it. The smaller the relative dielectric constant, the faster the signal transmission speed; the smaller the dielectric loss factor, the higher the allowable transmission frequency when the loss power of the signal during transmission remains constant, that is, at the same frequency, the smaller the dielectric loss value, the lower the distortion rate during signal transmission. In recent years, various electronic information product technologies have developed rapidly, and higher requirements have been placed on PCB.

[0003] As one of the basic materials of the electronic information industry, the manufacturing technology and performance of high-frequency application products of copper clad laminates have a vital impact on the development of the electronics industry. Traditional copper clad laminates such as epoxy / glass fiber systems and phenolic / paper systems are widely used due to mature equipment and processes and low cost. However, in high-frequency and high-speed environments, their disadvantages such as large dielectric constant and dielectric loss, poor heat resistance and poor moisture resistance are gradually exposed. Research and development of copper clad laminate materials with excellent high-frequency performance is of great significance to the development of industries such as electronic communications and supercomputers that require high signal transmission speed, transmission loss and transmission accuracy. Epoxy resin is a high molecular polymer. After curing, epoxy resin has many outstanding properties, such as strong adhesion to metal, chemical corrosion resistance, high mechanical strength, good electrical insulation, etc. However, epoxy resin has poor heat resistance, high dielectric constant and dielectric loss, which affect the application of epoxy resin. Polyphenylene ether has extremely low dielectric constant, dielectric loss and water absorption rate as well as high heat resistance. Therefore, the dielectric properties of epoxy resin can be improved by using polyphenylene ether to modify epoxy resin. However, polyphenylene ether and epoxy resin are thermodynamically incompatible systems, which not only affects the physical and mechanical properties of the copper clad laminate, but also affects the adhesion between the copper clad laminate and the copper foil. Summary of the invention

[0004] The object of the present invention is to provide a copper clad laminate for a printed circuit board and a preparation method thereof, so as to solve the following technical problems: In the prior art, polyphenylene ether is added to epoxy resin to reduce the dielectric constant, dielectric loss, water absorption rate and improve heat resistance of the material. However, polyphenylene ether and epoxy resin belong to a thermodynamically incompatible system, which reduces the physical and mechanical properties of the copper clad laminate and the bonding strength between the copper plate and the copper foil.

[0005] The purpose of the present invention can be achieved through the following technical solutions: A method for preparing a copper clad laminate for a printed circuit board comprises the following steps: S1: The reinforcing material is immersed in the adhesive solution and then dried to obtain a prepreg; S2: hot pressing the prepreg and the copper foil to obtain a copper clad laminate; The preparation method of the glue liquid comprises the following steps: according to the raw material ratio of the glue liquid, epoxy resin, terminal vinyl polyphenylene ether, bifunctional silica and organic solvent are blended, the temperature is raised to 70-80°C, a curing agent and a curing accelerator are added, the temperature is controlled at 40-60°C, stirred for 10-30 minutes, sieved, and the glue liquid is obtained.

[0006] As a further solution of the present invention: the glue liquid includes the following raw materials in parts by weight: 15-20 parts of vinyl-terminated polyphenylene ether, 20-25 parts of epoxy resin, 20-25 parts of bifunctional silica, 15-25 parts of organic solvent, 0.3-0.6 parts of curing agent, and 0.05-0.1 parts of curing accelerator; the fineness of the glue liquid is less than 20um.

[0007] As a further solution of the present invention: the curing agent is 4,4'-diaminodiphenyl sulfone; the curing accelerator is 2-methylimidazole; and the organic solvent is N,N-dimethylformamide.

[0008] As a further scheme of the present invention: the preparation method of vinyl-terminated polyphenylene ether comprises the following steps: adding polyphenylene ether and toluene into a reaction kettle, controlling the temperature to 50-60°C and stirring to dissolve, mixing sodium hydroxide, deionized water and dichloromethane and adding them into the reaction kettle, keeping the temperature for reaction for 0.5-1h, adding tetrabutylammonium bromide and p-chloromethylstyrene, keeping the temperature for reaction for 3-6h, extracting with ethanol, filtering and drying to obtain vinyl-terminated polyphenylene ether.

[0009] As a further embodiment of the present invention, the addition ratio of polyphenylene ether, toluene, sodium hydroxide, deionized water, dichloromethane, tetrabutylammonium bromide and p-chloromethylstyrene is 10 g: 20-40 mL: 20-40 g: 50-100 mL: 15-30 mL: 0.35-0.5 g: 20-30 g.

[0010] As a further embodiment of the present invention: the preparation method of bifunctional silica comprises the following steps: B1: Add nano-silica, ether and succinic anhydride into a reaction kettle and disperse them evenly, control the temperature at 20-30°C, keep the temperature for 2-4 hours under stirring, filter and dry to obtain carboxylated nano-silica; B2: Add carboxylated nano-silica, 3-aminopropyltrimethoxysilane, tetrahydrofuran, and dicyclohexylcarbodiimide into a reaction kettle and disperse them evenly. Control the temperature at 20-30° C., keep the temperature for 3-6 hours under stirring conditions, wash, and dry to obtain a silica intermediate. B3: Add the silica intermediate and dimethyl sulfoxide into the reaction kettle and disperse them evenly. Add 3-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane into the reaction kettle, control the temperature at 50-60°C, keep warm for 12-18 hours under stirring, add ammonium fluoride, cool to room temperature, react for 12-24 hours under stirring, filter and dry to obtain bifunctional silica.

[0011] As a further solution of the present invention: the addition ratio of nano-silicon dioxide, ether and succinic anhydride in B1 is 10g:50-100mL:4-8g.

[0012] As a further solution of the present invention: the addition ratio of carboxylated nano-silica, 3-aminopropyltrimethoxysilane, tetrahydrofuran, and dicyclohexylcarbodiimide in B2 is 10g:10-12mL:100-200mL:0.8-1g.

[0013] As a further embodiment of the present invention: the addition ratio of the silica intermediate, dimethyl sulfoxide, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane and ammonium fluoride in B3 is 10 g: 50-100 mL: 5-10 mL: 5-10 mL: 1-1.2 g.

[0014] As a further solution of the present invention: the specific step of drying in S1 is: baking at 150-190° C. for 30-60 min to volatilize the solvent.

[0015] As a further solution of the present invention: the specific steps of the hot pressing treatment in S2 are: hot pressing for 1.5-2h at a pressure of 20-25MPa and a temperature of 180-190°C.

[0016] As a further solution of the present invention: the reinforcing material is an alkali-free glass fiber cloth which is successively subjected to high-temperature dewaxing and cleaning and the surface of which is organically treated with a silane coupling agent solution.

[0017] A copper clad laminate for a printed circuit board is made by any one of the above-mentioned preparation methods.

[0018] Beneficial effects of the present invention: The present invention utilizes succinic anhydride to open the ring and graft carboxyl groups on the surface of nano-silica to obtain carboxylated nano-silica; the present invention utilizes carboxyl groups on the surface of carboxylated nano-silica to react with the amino groups of 3-aminopropyltrimethoxysilane to obtain a silica intermediate; and then reacts the silica intermediate with 3-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane by a sol-gel method to prepare bifunctional silica. The present invention utilizes Williamson reaction to vinyl-modify the end groups of polyphenylene ether to obtain vinyl-terminated polyphenylene ether.

[0019] The present invention utilizes a phenolic epoxy resin whose main chain is composed of benzene rings, which has the advantage of good heat resistance; the present invention utilizes terminal vinyl polyphenylene ether to modify the epoxy resin, which not only improves the heat resistance and dielectric properties of the epoxy resin, but also improves the compatibility of the polyphenylene ether and the epoxy resin, and reduces the phase separation phenomenon between the two; the present invention performs organic treatment on the inorganic filler silicon dioxide, improves the compatibility between the resin and the inorganic filler, reduces the gap between the filler and the resin matrix, and improves the comprehensive performance of the composite substrate; the present invention performs organic silicon modification on the surface of silicon dioxide, which can effectively reduce the dielectric constant and dielectric loss factor of the polymer, and S The i-O-Si cross-linked inorganic core can give the polymer good heat resistance and mechanical properties; the present application uses bifunctional silica as a cross-linking agent to cross-link polyphenylene ether with epoxy resin to obtain a new type of resin, which is used as the resin material of the glue. The polyphenylene ether is cross-linked with the epoxy resin under the action of bifunctional silica to form an interpenetrating network structure that penetrates the epoxy resin cross-linked network structure. The compatibility between polyphenylene ether and epoxy resin is effectively improved, and silica is evenly dispersed in the continuous phase of epoxy resin and polyphenylene ether, which effectively improves the mechanical properties and dielectric properties of epoxy resin without sacrificing the thermal stability of the system. The present application performs surface treatment on the glass fiber used as a reinforcing material, covers a layer of surface treatment agent on its surface, improves the compatibility of the glass fiber cloth with the glue, and then enhances the bonding strength between the glass fiber cloth surface and the resin. DETAILED DESCRIPTION

[0020] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1 The preparation method of bifunctional silica comprises the following steps: B1: 10 g of nano-silica, 50 mL of ether and 4 g of succinic anhydride were added to a reaction kettle and dispersed evenly. The temperature was controlled at 20°C and kept under stirring for 2 h. The mixture was filtered and dried to obtain carboxylated nano-silica. B2: 10 g of carboxylated nano-silica, 10 mL of 3-aminopropyltrimethoxysilane, 100 mL of tetrahydrofuran, and 0.8 g of dicyclohexylcarbodiimide were added to a reaction kettle and dispersed evenly. The temperature was controlled at 20°C and kept warm for 3 h under stirring conditions. The silica intermediate was washed and dried to obtain a silica intermediate. B3: Add 10g of silica intermediate and 50mL of dimethyl sulfoxide into a reaction kettle and disperse them evenly. Add 5mL of 3-aminopropyltrimethoxysilane and 10mL of 3-mercaptopropyltrimethoxysilane into the reaction kettle. Control the temperature to 55°C and keep it warm for 12h under stirring. Add 1g of ammonium fluoride and cool it to room temperature. React it for 12h under stirring. Filter and dry to obtain bifunctional silica.

[0022] Example 2 The preparation method of bifunctional silica comprises the following steps: B1: 10 g of nano-silica, 70 mL of ether and 6 g of succinic anhydride were added to a reaction kettle and dispersed evenly. The temperature was controlled at 25°C and kept under stirring for 3 h. The mixture was filtered and dried to obtain carboxylated nano-silica. B2: 10 g of carboxylated nano-silica, 11 mL of 3-aminopropyltrimethoxysilane, 150 mL of tetrahydrofuran, and 0.9 g of dicyclohexylcarbodiimide were added to a reaction kettle and dispersed evenly. The temperature was controlled at 25°C and kept warm for 4.5 h under stirring conditions. The silica intermediate was washed and dried to obtain a silica intermediate. B3: Add 10g of silica intermediate and 70mL of dimethyl sulfoxide into a reaction kettle and disperse them evenly. Add 5mL of 3-aminopropyltrimethoxysilane and 10mL of 3-mercaptopropyltrimethoxysilane into the reaction kettle. Control the temperature to 55°C and keep it warm for 15h under stirring. Add 1.1g of ammonium fluoride and cool it to room temperature. React for 18h under stirring. Filter and dry to obtain bifunctional silica.

[0023] Example 3 The preparation method of bifunctional silica comprises the following steps: B1: 10 g of nano-silica, 100 mL of ether and 8 g of succinic anhydride were added to a reaction kettle and dispersed evenly. The temperature was controlled at 30°C and kept under stirring for 4 h. The mixture was filtered and dried to obtain carboxylated nano-silica. B2: 10 g of carboxylated nano-silica, 12 mL of 3-aminopropyltrimethoxysilane, 200 mL of tetrahydrofuran, and 1 g of dicyclohexylcarbodiimide were added to a reaction kettle and dispersed evenly. The temperature was controlled at 30°C and kept warm for 6 h under stirring. The silica intermediate was washed and dried to obtain a silica intermediate. B3: Add 10g of silica intermediate and 100mL of dimethyl sulfoxide into a reaction kettle and disperse them evenly. Add 10mL of 3-aminopropyltrimethoxysilane and 10mL of 3-mercaptopropyltrimethoxysilane into the reaction kettle. Control the temperature at 60°C and keep it warm for 18h under stirring. Add 1.2g of ammonium fluoride and cool it to room temperature. React it for 24h under stirring. Filter and dry to obtain bifunctional silica.

[0024] Example 4 The preparation method of the glue solution comprises the following steps: A1: Add 10g polyphenylene ether (molecular weight 30000) and 30mL toluene into a reactor, control the temperature to 55℃ and stir to dissolve, mix 30g sodium hydroxide, 60mL deionized water and 30mL dichloromethane and add into the reactor, keep warm for 0.5h, add 0.5g tetrabutylammonium bromide and 30g p-chloromethylstyrene, keep warm for 3h, extract with ethanol, filter and dry to obtain vinyl-terminated polyphenylene ether; A2: 20 g of vinyl-terminated polyphenylene ether, 20 g of epoxy resin (phenolic epoxy resin F-51), 20 g of bifunctional silica prepared in Example 1, and 25 g of N,N-dimethylformamide were blended, the temperature was raised to 75°C, 0.3 g of 4,4'-diaminodiphenyl sulfone and 0.05 g of 2-methylimidazole were added, the temperature was controlled at 50°C, stirred for 10 min, and sieved to make the fineness of the glue solution less than 20 um to obtain a glue solution.

[0025] Example 5 The preparation method of the glue solution comprises the following steps: A1: Add 10g polyphenylene ether (molecular weight 30000) and 30mL toluene into a reactor, control the temperature to 55℃ and stir to dissolve, mix 30g sodium hydroxide, 60mL deionized water and 30mL dichloromethane and add into the reactor, keep warm for 0.5h, add 0.5g tetrabutylammonium bromide and 30g p-chloromethylstyrene, keep warm for 3h, extract with ethanol, filter and dry to obtain vinyl-terminated polyphenylene ether; A2: 20 g of vinyl-terminated polyphenylene ether, 20 g of epoxy resin (phenolic epoxy resin F-51), 20 g of bifunctional silica prepared in Example 2, and 25 g of N,N-dimethylformamide were blended, the temperature was raised to 75°C, 0.3 g of 4,4'-diaminodiphenyl sulfone and 0.05 g of 2-methylimidazole were added, the temperature was controlled at 50°C, stirred for 10 min, and sieved to make the fineness of the glue solution less than 20 um to obtain a glue solution.

[0026] Example 6 The preparation method of the glue solution comprises the following steps: A1: Add 10g polyphenylene ether (molecular weight 30000) and 30mL toluene into a reactor, control the temperature to 55℃ and stir to dissolve, mix 30g sodium hydroxide, 60mL deionized water and 30mL dichloromethane and add into the reactor, keep warm for 0.5h, add 0.5g tetrabutylammonium bromide and 30g p-chloromethylstyrene, keep warm for 3h, extract with ethanol, filter and dry to obtain vinyl-terminated polyphenylene ether; A2: 20 g of vinyl-terminated polyphenylene ether, 20 g of epoxy resin (phenolic epoxy resin F-51), 20 g of bifunctional silica prepared in Example 3, and 25 g of N,N-dimethylformamide were blended, the temperature was raised to 75°C, 0.3 g of 4,4'-diaminodiphenyl sulfone and 0.05 g of 2-methylimidazole were added, the temperature was controlled at 50°C, stirred for 10 min, and sieved to make the fineness of the glue solution less than 20 um to obtain a glue solution.

[0027] Embodiment 7 A method for preparing a copper clad laminate for a printed circuit board comprises the following steps: S1: Bake the alkali-free glass fiber cloth at 450℃ for 10 minutes to remove the paraffin on the surface of the glass fiber cloth, enhance the surface tension of the glass fiber cloth, and make the contact between the resin and the glass fiber cloth closer; S2: The preparation method of the silane coupling agent modified liquid comprises the following steps: hydrolyzing 10 mL of vinyl trimethoxysilane and 90 mL of a 95 wt% ethanol aqueous solution at room temperature for 1 hour to obtain a silane coupling agent modified liquid; immersing the alkali-free glass fiber cloth after high-temperature dewaxing and cleaning in the silane coupling agent modified liquid for 5 minutes, drying, placing at 120° C., and baking for 30 minutes to obtain a pretreated glass fiber cloth; S3: After the pretreated glass fiber arrangement is immersed in the adhesive solution prepared in Example 4, it is baked at 190° C. for 30 minutes to volatilize the solvent to obtain a prepreg; S4: stack the eight prepregs prepared in step S3, cover them with copper foil, and hot-press them for 1.5 hours at a pressure of 20 MPa and a temperature of 190° C. to obtain a copper clad laminate.

[0028] Embodiment 8 A method for preparing a copper clad laminate for a printed circuit board comprises the following steps: S1: Bake the alkali-free glass fiber cloth at 450℃ for 10 minutes to remove the paraffin on the surface of the glass fiber cloth, enhance the surface tension of the glass fiber cloth, and make the contact between the resin and the glass fiber cloth closer; S2: The preparation method of the silane coupling agent modified liquid comprises the following steps: hydrolyzing 10 mL of vinyl trimethoxysilane and 90 mL of a 95 wt% ethanol aqueous solution at room temperature for 1 hour to obtain a silane coupling agent modified liquid; immersing the alkali-free glass fiber cloth after high-temperature dewaxing and cleaning in the silane coupling agent modified liquid for 5 minutes, drying, placing at 120° C., and baking for 30 minutes to obtain a pretreated glass fiber cloth; S3: After the pretreated glass fiber arrangement is immersed in the adhesive solution prepared in Example 5, it is baked at 190° C. for 30 minutes to volatilize the solvent to obtain a prepreg; S4: stack the eight prepregs prepared in step S3, cover them with copper foil, and hot-press them for 1.5 hours at a pressure of 20 MPa and a temperature of 190° C. to obtain a copper clad laminate.

[0029] Embodiment 9 A method for preparing a copper clad laminate for a printed circuit board comprises the following steps: S1: Bake the alkali-free glass fiber cloth at 450℃ for 10 minutes to remove the paraffin on the surface of the glass fiber cloth, enhance the surface tension of the glass fiber cloth, and make the contact between the resin and the glass fiber cloth closer; S2: The preparation method of the silane coupling agent modified liquid comprises the following steps: hydrolyzing 10 mL of vinyl trimethoxysilane and 90 mL of a 95 wt% ethanol aqueous solution at room temperature for 1 hour to obtain a silane coupling agent modified liquid; immersing the alkali-free glass fiber cloth after high-temperature dewaxing and cleaning in the silane coupling agent modified liquid for 5 minutes, drying, placing at 120° C., and baking for 30 minutes to obtain a pretreated glass fiber cloth; S3: After the pretreated glass fiber arrangement is immersed in the adhesive solution prepared in Example 6, it is baked at 190° C. for 30 minutes to volatilize the solvent to obtain a prepreg; S4: stack the eight prepregs prepared in step S3, cover them with copper foil, and hot-press them for 1.5 hours at a pressure of 20 MPa and a temperature of 190° C. to obtain a copper clad laminate.

[0030] Comparative Example 1 The preparation method of bifunctional silica comprises the following steps: 10 g of nano-silica, 5 mL of 3-aminopropyltrimethoxysilane, 10 mL of 3-mercaptopropyltrimethoxysilane, 90 mL of anhydrous ethanol and 10 mL of deionized water were added into a reaction kettle, the temperature was controlled at 55°C, kept under stirring for 15 h, cooled to room temperature, reacted under stirring for 18 h, filtered and dried to obtain bifunctional silica.

[0031] Comparative Example 2 The preparation method of the glue solution comprises the following steps: A1: Add 10g polyphenylene ether (molecular weight 30000) and 30mL toluene into a reactor, control the temperature to 55℃ and stir to dissolve, mix 30g sodium hydroxide, 60mL deionized water and 30mL dichloromethane and add into the reactor, keep warm for 0.5h, add 0.5g tetrabutylammonium bromide and 30g p-chloromethylstyrene, keep warm for 3h, extract with ethanol, filter and dry to obtain vinyl-terminated polyphenylene ether; A2: 20 g of vinyl-terminated polyphenylene ether, 20 g of epoxy resin (phenolic epoxy resin F-51), 20 g of bifunctional silica prepared in Comparative Example 1, and 25 g of N,N-dimethylformamide were blended, the temperature was raised to 75°C, 0.3 g of 4,4'-diaminodiphenyl sulfone and 0.05 g of 2-methylimidazole were added, the temperature was controlled at 50°C, stirred for 10 min, and sieved to make the fineness of the glue liquid less than 20 um to obtain a glue liquid.

[0032] Comparative Example 3 The preparation method of the glue solution comprises the following steps: 20 g of polyphenylene ether (molecular weight 30,000), 20 g of epoxy resin (phenolic epoxy resin F-51), 20 g of bifunctional silica prepared in Example 2, and 25 g of N,N-dimethylformamide were blended, and the temperature was raised to 75° C., 0.3 g of 4,4'-diaminodiphenyl sulfone and 0.05 g of 2-methylimidazole were added, the temperature was controlled at 50° C., stirred for 10 min, and sieved to make the fineness of the glue solution less than 20 um to obtain a glue solution.

[0033] Comparative Example 4 The preparation method of the glue solution comprises the following steps: A1: Add 10g polyphenylene ether (molecular weight 30000) and 30mL toluene into a reactor, control the temperature to 55℃ and stir to dissolve, mix 30g sodium hydroxide, 60mL deionized water and 30mL dichloromethane and add into the reactor, keep warm for 0.5h, add 0.5g tetrabutylammonium bromide and 30g epichlorohydrin, keep warm for 3h, extract with ethanol, filter and dry to obtain epoxy-terminated polyphenylene ether; A2: 20g of epoxy-terminated polyphenylene ether, 20g of epoxy resin (phenolic epoxy resin F-51), 20g of bifunctional silica prepared in Comparative Example 1, and 25g of N,N-dimethylformamide were blended, the temperature was raised to 75°C, 0.3g of 4,4'-diaminodiphenyl sulfone and 0.05g of 2-methylimidazole were added, the temperature was controlled at 50°C, stirred for 10min, and sieved to make the fineness of the glue liquid less than 20um to obtain a glue liquid.

[0034] Comparative Example 5 Compared with Example 8, only the glue prepared in Example 5 used in Example 8 is replaced by the glue prepared in Comparative Example 2 in equal amount, and the other components and preparation method are completely the same as those in Example 8.

[0035] Comparative Example 6 Compared with Example 8, only the glue prepared in Example 5 used in Example 8 is replaced by the glue prepared in Comparative Example 3 in equal amount, and the other components and preparation method are completely the same as those in Example 8.

[0036] Comparative Example 7 Compared with Example 8, only the glue prepared in Example 5 used in Example 8 is replaced by the glue prepared in Comparative Example 4 in equal amount, and the other components and preparation method are completely the same as those in Example 8.

[0037] Performance Testing (1) Water absorption rate: According to IPC-TM-650 2.6.2.1, the test standard for the determination of water absorption rate of copper foil plastic laminates, the copper clad laminate is processed into a sample with a size of 50×50 mm. The edges of the sample are polished smooth with 400 sandpaper and dried in a prefabricated oven. The mass of the sample is weighed as m1. The sample is immersed in deionized water for 24 hours. After being taken out and the surface moisture is wiped off, the mass of the sample is weighed as m2, and the water absorption rate η of the sample is calculated according to the following formula: In the formula, η is water absorption rate, %; m1 is the mass of the sample before immersion, g; m2 is the mass of the sample after immersion, g; the test results are shown in Table 1; (2) Microwave dielectric properties: According to IPC-TM-650 2.5.5.5 stripline test of permittivity and loss angle, tested by stripline resonance method, the test frequency covers the 1-18 GHz range, and the test results are shown in Table 1; (3) Heat resistance: 10 mg of the samples obtained by curing the glue prepared in Examples 4-6 and Comparative Examples 2-5 were heated from 30°C to 700°C at a rate of 5°C / min under a nitrogen atmosphere, and the temperature at which the sample lost 5 wt% of its weight was recorded as , the test results are shown in Table 1; Table 1: Statistical table of performance test data of Examples 4-6 and Comparative Examples 2-5 It can be seen from Table 1 that the glue prepared in the present application has low water absorption, low dielectric constant and dielectric loss and excellent heat resistance after curing.

[0038] (4) Peel strength: Test according to IPC-TM-650 2.4.8 for metal foil coated plates, with a loading speed of 50 mm / min and a peel length greater than 25 mm. Record the minimum load force and calculate the peel strength N according to the following formula: Wherein, N-peel strength, N / mm; Lm-minimum loading load, N; Ws-peel tape test width, mm; the test results are shown in Table 2; (5) Bending strength: Tested according to IPC-TM-650 2.4.4, using a microcomputer-controlled electronic universal material testing machine with a test speed of 0.5 mm / min. The average bending strength σ is calculated according to the following formula: Wherein, σ-bending strength, MPa; P-breaking load, N; L-span, mm; B-specimen width, mm; H-specimen thickness, mm; the test results are shown in Table 2; Table 2: Statistical table of mechanical properties test data of Examples 7-9 and Comparative Examples 5-7 It can be seen from Table 2 that the copper clad laminate prepared in the present application has good mechanical properties, and the adhesive has good bonding strength with the copper foil and the glass fiber cloth.

[0039] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A method for preparing a copper clad laminate for a printed circuit board, characterized in that: The steps include: S1: The reinforcing material is immersed in the adhesive solution and then dried to obtain a prepreg; S2: hot pressing the prepreg and the copper foil to obtain a copper clad laminate; The preparation method of the adhesive comprises the following steps: according to the raw material ratio of the adhesive, epoxy resin, vinyl-terminated polyphenylene ether, bifunctional silica and organic solvent are mixed, the temperature is raised to 70-80° C., a curing agent and a curing accelerator are added, the temperature is controlled at 40-60° C., stirred for 10-30 minutes, and sieved to obtain the adhesive.

2. The method for preparing a copper clad laminate for a printed circuit board according to claim 1, characterized in that: The glue comprises the following raw materials in parts by weight: 15-20 parts of vinyl-terminated polyphenylene ether, 20-25 parts of epoxy resin, 20-25 parts of bifunctional silica, 15-25 parts of organic solvent, 0.3-0.6 parts of curing agent, and 0.05-0.1 parts of curing accelerator; the fineness of the glue is less than 20um.

3. The method for preparing a copper clad laminate for a printed circuit board according to claim 1, characterized in that: The curing agent is 4,4'-diaminodiphenyl sulfone; the curing accelerator is 2-methylimidazole; and the organic solvent is N,N-dimethylformamide.

4. The method for preparing a copper clad laminate for a printed circuit board according to claim 1, characterized in that: The preparation method of vinyl-terminated polyphenylene ether comprises the following steps: adding polyphenylene ether and toluene into a reaction kettle, controlling the temperature to 50-60 DEG C for stirring and dissolving, mixing sodium hydroxide, deionized water and dichloromethane and adding them into the reaction kettle, keeping the temperature for reaction for 0.5-1h, adding tetrabutylammonium bromide and p-chloromethylstyrene, keeping the temperature for reaction for 3-6h, extracting with ethanol, filtering and drying to obtain vinyl-terminated polyphenylene ether.

5. The method for preparing a copper clad laminate for a printed circuit board according to claim 1, characterized in that: The addition ratio of polyphenylene ether, toluene, sodium hydroxide, deionized water, dichloromethane, tetrabutylammonium bromide, and p-chloromethylstyrene is 10g:20-40mL:20-40g:50-100mL:15-30mL:0.35-0.5g:20-30g.

6. The method for preparing a copper clad laminate for a printed circuit board according to claim 1, characterized in that: The preparation method of the bifunctional silica comprises the following steps: B1: Add nano-silica, ether and succinic anhydride into a reaction kettle and disperse them evenly, control the temperature at 20-30°C, keep the temperature for 2-4 hours under stirring, filter and dry to obtain carboxylated nano-silica; B2: Add carboxylated nano-silica, 3-aminopropyltrimethoxysilane, tetrahydrofuran, and dicyclohexylcarbodiimide into a reaction kettle and disperse them evenly. Control the temperature at 20-30° C., keep the temperature for 3-6 hours under stirring conditions, wash, and dry to obtain a silica intermediate. B3: Add the silica intermediate and dimethyl sulfoxide into the reaction kettle and disperse them evenly. Add 3-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane into the reaction kettle, control the temperature at 50-60°C, keep warm for 12-18 hours under stirring, add ammonium fluoride, cool to room temperature, react for 12-24 hours under stirring, filter and dry to obtain bifunctional silica.

7. The method for preparing a copper clad laminate for a printed circuit board according to claim 6, characterized in that: The addition ratio of nano-silica, ether and succinic anhydride in B1 is 10 g: 50-100 mL: 4-8 g.

8. The method for preparing a copper clad laminate for a printed circuit board according to claim 6, characterized in that: The addition ratio of carboxylated nano-silica, 3-aminopropyltrimethoxysilane, tetrahydrofuran, and dicyclohexylcarbodiimide in B2 is 10 g: 10-12 mL: 100-200 mL: 0.8-1 g.

9. The method for preparing a copper clad laminate for a printed circuit board according to claim 6, characterized in that: The addition ratio of the silica intermediate, dimethyl sulfoxide, 3-aminopropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and ammonium fluoride in B3 is 10 g: 50-100 mL: 5-10 mL: 5-10 mL: 1-1.2 g.

10. A copper clad laminate for a printed circuit board, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Semi-curing sheet for fire-retardant resin-based copper clad laminates, and preparation method thereof

    CN107722560A

  • Flame-retarded resin glue solution used for copper-clad plate and preparation method of flame-retarded resin glue solution

    CN107759978A

  • Thermosetting resin composition, prepreg containing thermosetting resin composition and copper-clad plate containing thermosetting resin composition

    CN118271722A

  • Copper-clad laminate using modified polyphenylene oxide

    WO2015046953A1

  • Resin composition, prepreg, laminated board, preparation method for prepreg, preparation method for laminated board and application thereof

    WO2022000629A1

Cited By

  • Copper-clad plate with low dielectric constant and high performance and preparation method thereof

    CN120116591A

  • High-wettability prepreg and preparation method thereof

    CN120464135A

  • High-performance high-frequency flexible polyimide-based copper-clad plate and preparation method thereof

    CN121157497A

  • High-performance high-frequency flexible polyimide-based copper-clad plate and preparation method thereof

    CN121157497B